Righteous Way of Jalapana Vidhi- An Ayurvedic Review - Supriya.B M; Prabhu C Nagalapur; Chandrashekaraddi S Karamudi (AYUSHDHARA, 2022)
Water is origin of life, from where whole unicellular to multi cellular organism, whole animal and plant kingdoms came. Sarvadravyum panchamahabouthikatwam, Water is composed of all Mahabhutha. Water is considered as life for human being, so it can’t be contraindicated completely in any bodily condition. In this present era, due to fast and mechanical life people are following irregular life styles and improper dietary habits because of which there is a impairement in the physiological function of the body. Water is source of health if taken at right time and in appropriate quantity. It is believed that the water possesses ability to treat various diseases. Ayurvedic literature gives very experienced knowledge about time, quantity and appropriate water intake concerning health as well as improper water ingestion relating to disorders. Hence an attempt is made to review the Jalapana vidhi in all Ayurvedic literatures